Antioxidant activities and polyphenolic identification by UPLC-MS/MS of autoclaved brewers’ spent grain - Naibaho Joncer; Wojdyło Aneta; Korzeniowska Małgorzata; Laaksonen Oskar; Föste Maike; Kütt Mary-Liis; Yang Baoru (Academic Press, 2022)
Autoclave treatment (AT) modified the dietary fiber composition of brewers' spent grain (BSG), impacting its techno-processing properties. However, its impact on antioxidant properties and stability of polyphenolic compounds remain unclear. This study aimed to evaluate the influence of AT on several antioxidant activities and polyphenolic composition. The results showed that AT increased ORAC (oxygen radical absorbance capacity), ABTS (2,2′-Azinobis-(3-ethylbenzthiazoline-6-sulfonic acid), and FRAP (ferric-reducing antioxidant power) value upto 7 folds compared to the untreated BSG. The lower temperature degraded the amount of flavan-3-ols and phenolic acids. However, AT at 110 °C and 130 °C upgraded the phenolic acids upto 4 and 11 folds respectively. Higher temperature also induced the formation of benzoic acid and (+)-catechin. UPLC-MS/MS identified several phenolic acids including syringic acid, benzoic acid, coumaric acid, ferulic acid and its derivatives, and flavan-3-ols such as (+)-catechin and (−)-epicatechin. In conclusion, AT improved the bioactivity of BSG, enhanced the amount of certains phenolic compounds and released the bioactive compounds from BSG matrices thus offering a higher benefit for industry to utilise autoclaved BSG.